A review on crucial aspects in up-scaling cultured meat production / Syazwani Washi and Naemaa Mohamad - Washi, Syazwani; Mohamad, Naemaa (2021)
Current meat consumption pattern is putting a lot of burden on the environment by taking up a lot of resources and releasing emissions from activities such as rearing animals that cause environmental pollution. One of the alternatives on the market is plant-based meat which is made from plant ingredients which is favourable among vegetarians. However, meat eaters are not satisfied with plant- based meat and are looking for other options. Cultured meat is introduced to overcome the issue related to conventional meat and provide a better alternative to meat. No massive animal rearing is needed to produce cultured meat since it is produced by cell culturing methods from cells obtained through painless biopsy on living animals. Many studies are conducted to produce cultured meat for commercialization and to up-scale the production of cultured meat. Current method to produce cultured meat is on the lab-scale and very expensive. Up-scaling of cultured meat must ensure that it is cost- effective, sustainable, and acceptable. This review paper highlights the important aspects in up- scaling cultured meat production from maintaining the stemness of satellite cells to sustainable alternatives of cell growth medium and scaffold as well as components that improved the cell growth. The cost for cultured meat is still expensive, but by making changes through possible alternatives on the materials used can reduce the cost and make cultured meat acceptable by the public.